Ionic liquid, solvent for lithium ion battery, lithium ion battery electrolyte, lithium ion battery and electric equipment
By using piperidine groups with high oxidation potential and ionic liquids that stabilize the interface film, the problems of oxidative decomposition and flatulence of lithium-ion batteries under high voltage and high temperature conditions are solved, and better cycle performance and safety performance are achieved.
Patent Information
- Application Number
- CN202411454235.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-17
AI Technical Summary
Traditional lithium-ion batteries are prone to oxidation and decomposition, gas production and flatulence under high voltage and high temperature conditions, resulting in a degradation of circulation performance.
Ionic liquids with piperidine groups with high oxidation potential and difluoroxalate borate or tetrafluoroxalate phosphate are used to form a stable interface film, neutralize the acid in the electrolyte, and improve the conductivity.
Under high voltage and high temperature conditions, ionic liquids can exist stably, improve battery cycle performance, reduce gas expansion problems, and improve safety performance.
Smart Images

Figure CN119330911A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion battery manufacturing, and in particular to an ionic liquid, a solvent for lithium-ion batteries, an electrolyte for lithium-ion batteries, a lithium-ion battery, and electrical equipment. Background Art
[0002] Lithium-ion batteries currently dominate the fields of power and energy storage, and with technological innovation, efforts have been made to develop lithium-ion batteries that can be used under high voltage conditions (≥4.9V). However, traditional solvents (such as EC, EMC or DEC, etc.) are easily oxidized and decomposed and produce gas under high voltage, resulting in severe bloating of the corresponding batteries. Based on this, new fluorinated solvents (such as FEMC, FPC or FEC, etc.) have been proposed. Although these fluorinated solvents have a higher oxidation potential and can exist stably under high voltage, they have low electrical conductivity and are unstable and easy to decompose and produce gas under high temperature conditions, which affects the cycle performance of the corresponding battery under high voltage and high temperature conditions. Therefore, there is an urgent need to develop a new solvent that can exist stably under high voltage and high temperature conditions and has high electrical conductivity. Summary of the invention
[0003] The purpose of the present application is to provide an ionic liquid, a solvent for lithium-ion batteries, an electrolyte for lithium-ion batteries, a lithium-ion battery and electrical equipment. The ionic liquid can stably exist under high voltage and high temperature conditions and has a high electrical conductivity, so that the corresponding battery has a relatively excellent cycle performance when used under high voltage and high temperature conditions. At the same time, it can also effectively improve the problem that the corresponding battery is prone to flatulence when used under high voltage and high temperature conditions.
[0004] The embodiment of the present application is implemented as follows:
[0005] In a first aspect, an embodiment of the present application provides an ionic liquid, including ionic liquid 1 and / or ionic liquid 2, wherein the structural formula of ionic liquid 1 is as shown in Formula I, and the structural formula of ionic liquid 2 is as shown in Formula II:
[0006]
[0007] In the above technical scheme, the ionic liquid has the above-mentioned specific structure, and the piperidine group in the structure has the advantage of high oxidation potential (i.e., it can stably exist under high voltage), and at the same time, the N atom in the piperidine structure can neutralize the acid produced in the electrolyte (contribute to the problem of decomposition and gas production), and difluoro oxalate borate and / or tetrafluoro oxalate phosphate can form an interface film with good thermal stability on the positive and negative electrode surfaces (the interface film can reduce the direct contact between the ionic liquid and the positive and negative electrodes, and also contribute to the problem of decomposition and gas production), so that the ionic liquid can stably exist under high voltage and high temperature conditions, in addition, the piperidine group in the structure also has the advantage of higher conductivity. Therefore, the ionic liquid provided by the embodiment of the present application can stably exist under high voltage and high temperature conditions and have higher conductivity concurrently, so that the corresponding battery has a relatively excellent cycle performance when applied under high voltage and high temperature conditions, and at the same time, the corresponding battery can also effectively improve the problem of easy inflation when applied under high voltage and high temperature conditions.
[0008] In a second aspect, an embodiment of the present application provides a solvent for a lithium-ion battery, comprising the ionic liquid and an organic solvent provided in the embodiment of the first aspect.
[0009] In the above technical scheme, the solvent for lithium-ion batteries contains, in addition to the organic solvent, the ionic liquid provided in the first embodiment. By taking advantage of the unique advantages of the ionic liquid, the solvent for lithium-ion batteries can stably exist under high voltage and high temperature conditions and have a high electrical conductivity, thereby enabling the corresponding battery to have excellent cycle performance when used under high voltage and high temperature conditions. At the same time, it can also effectively improve the problem of the corresponding battery being prone to flatulence when used under high voltage and high temperature conditions.
[0010] In some optional embodiments, the mass percentage of the ionic liquid in the solvent is 30-50%.
[0011] In the above technical scheme, the mass percentage of the ionic liquid in the solvent is limited to a specific range, so that the solvent contains a relatively suitable mass percentage of the ionic liquid, thereby making the corresponding battery have a better cycle performance when used under high voltage and high temperature conditions and can also more effectively improve the problem of the corresponding battery being prone to flatulence when used under high voltage and high temperature conditions. At the same time, it can also make the corresponding battery have a relatively excellent safety performance.
[0012] In some optional embodiments, the organic solvent is selected from at least one of fluoroethylene carbonate, bisfluoroethylene carbonate, trifluoroethyl methyl carbonate, bis(2,2,2 trifluoroethyl) carbonate, 3,3,3 trifluoropropylene carbonate and methyl hexafluoroisopropyl carbonate.
[0013] Among the above technical solutions, the technical solutions provided in the embodiments of the present application are applicable to a wide variety of organic solvents and can provide a wide variety of feasible implementation plans, thereby facilitating the promotion and application of the technical solutions provided in the present application.
[0014] In a third aspect, an embodiment of the present application provides a lithium-ion battery electrolyte, comprising a lithium-ion battery solvent, a lithium salt, and an additive as provided in the embodiment of the second aspect.
[0015] In the above technical scheme, the lithium-ion battery electrolyte includes a lithium-ion battery solvent as provided in the second aspect embodiment. Since the solvent contains an ionic liquid with a specific structure, the corresponding battery has a relatively excellent cycle performance when used under high voltage and high temperature conditions. At the same time, it can also effectively improve the problem that the corresponding battery is prone to flatulence when used under high voltage and high temperature conditions.
[0016] In some optional embodiments, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorobis(oxalatophosphate), lithium tetrafluorooxalatophosphate, lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonyl)imide and lithium bis(oxalatoborate).
[0017] Among the above technical solutions, the technical solutions provided in the embodiments of the present application are applicable to a wide variety of lithium salts and can provide a wide variety of feasible implementation plans, thereby facilitating the promotion and application of the technical solutions provided in the present application.
[0018] In some optional embodiments, the mass percentage of lithium salt in the electrolyte is 10-18%.
[0019] In the above technical solution, the mass percentage of lithium salt in the electrolyte is limited to a specific range, so that the electrolyte contains lithium salt with a relatively suitable mass percentage, so that the electrolyte has relatively excellent electrical conductivity, and thus the corresponding battery has relatively excellent cycle performance when used under high voltage and high temperature conditions.
[0020] In some optional embodiments, the additive is selected from at least one of 1,3 propane sultone, 1,4 butane sultone, allyl 1,3 sultone, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluorooxalatephosphate, lithium difluorooxalatephosphate, tetravinylsilane, tripropylene phosphate, tetravinyltin, hexamethylene diisocyanate and difluoropyridine.
[0021] In the above technical solutions, the technical solutions provided in the embodiments of the present application are applicable to a wide variety of additives and can provide a wide variety of feasible implementation plans, thereby facilitating the promotion and application of the technical solutions provided in the present application.
[0022] In some optional embodiments, the mass percentage of the additive in the electrolyte is 0.5-5%.
[0023] In the above technical solution, the mass percentage of the additive in the electrolyte is limited to a specific range, so that the electrolyte contains additives with a relatively suitable mass percentage, so that the corresponding battery has relatively excellent cycle performance when used under high voltage and high temperature conditions.
[0024] In a fourth aspect, an embodiment of the present application provides a lithium-ion battery, comprising a shell, an electrode assembly, and an electrolyte as provided in the embodiment of the third aspect, wherein the electrode assembly is contained in the shell; and the electrolyte is contained in the shell.
[0025] In the above technical solution, the lithium-ion battery includes the electrolyte provided in the first aspect embodiment. With the unique advantages of the electrolyte, the lithium-ion battery has a relatively excellent cycle performance when used under high voltage and high temperature conditions. At the same time, it can also effectively improve the problem that the corresponding battery is prone to flatulence when used under high voltage and high temperature conditions.
[0026] In some optional embodiments, in the battery positive electrode of the electrode assembly, the positive electrode active material is selected from at least one of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel manganese oxide and lithium cobalt oxide.
[0027] Among the above technical solutions, the technical solution provided in the embodiment of the present application can be applied to the above-mentioned various positive electrode active material systems, providing more feasible implementation plans, thereby facilitating the promotion and application of the technical solution provided in the embodiment of the present application.
[0028] In some optional embodiments, in the battery negative electrode of the electrode assembly, the negative electrode active material is selected from at least one of graphite, soft carbon, hard carbon, silicon, silicon oxides and silicon-carbon composites.
[0029] Among the above technical solutions, the technical solution provided in the embodiment of the present application can be applied to the above-mentioned various negative electrode active material systems, providing more feasible implementation plans, thereby facilitating the promotion and application of the technical solution provided in the embodiment of the present application.
[0030] In a fifth aspect, an embodiment of the present application provides an electrical device, comprising a lithium-ion battery as provided in the embodiment of the fourth aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1The nuclear magnetic resonance spectrum of the ionic liquid 1 provided in Example 1 of the present application;
[0033] Figure 2 The nuclear magnetic resonance spectrum of ionic liquid 2 provided in Example 7 of the present application;
[0034] Figure 3 This is a comparison chart of the oxidation potentials of the electrolytes prepared in Example 5 and Comparative Example 1 provided in the present application. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0036] It should be noted that “and / or” in this application, such as “Feature 1 and / or Feature 2”, refers to the three situations of “Feature 1” alone, “Feature 2” alone, or “Feature 1” plus “Feature 2”.
[0037] In addition, in the description of the present application, unless otherwise specified, the meaning of "multiple" in "one or more" refers to two or more; the range of "value a ~ value b" includes the two end values "a" and "b", and the "unit" in "value a ~ value b + unit of measurement" represents the "unit of measurement" of both "value a" and "value b".
[0038] The following is a detailed description of an ionic liquid, a solvent for a lithium ion battery, an electrolyte for a lithium ion battery, a lithium ion battery, and an electrical device in accordance with an embodiment of the present application.
[0039] In a first aspect, an embodiment of the present application provides an ionic liquid, including ionic liquid 1 and / or ionic liquid 2, wherein the structural formula of ionic liquid 1 is as shown in Formula I, and the structural formula of ionic liquid 2 is as shown in Formula II:
[0040]
[0041] In the present application, the ionic liquid has the above-mentioned specific structure, and the piperidine group in the structure has the advantage of high oxidation potential (i.e., it can stably exist under high voltage), and at the same time, the N atom in the piperidine structure can neutralize the acid produced in the electrolyte (contribute to the problem of decomposition and gas production), and difluorooxalate borate and / or tetrafluorooxalate phosphate can form an interface film with good thermal stability on the surface of both positive and negative electrodes (the interface film can reduce the direct contact between the ionic liquid and the positive and negative electrodes, and also contribute to the problem of decomposition and gas production), so that the ionic liquid can stably exist under high voltage and high temperature conditions, in addition, the piperidine group in the structure also has the advantage of higher conductivity. Therefore, the ionic liquid provided by the embodiment of the present application can stably exist under high voltage and high temperature conditions and have higher conductivity, so that the corresponding battery has a relatively excellent cycle performance when applied under high voltage and high temperature conditions, and at the same time, the problem of easy flatulence expansion when the corresponding battery is applied under high voltage and high temperature conditions can also be effectively improved.
[0042] In order to better understand the technical solution, a specific preparation process is provided here for auxiliary explanation.
[0043] The preparation process of ionic liquid 1 comprises the following steps:
[0044] 0.1 mol of N-methylpiperidine and 0.1 mol of 1-bromomethane were added to 50 g of acetonitrile under a nitrogen atmosphere and then heated under reflux and stirred at 80°C for 24 hours. After the acetonitrile in the mixture was volatilized, an orange solid was obtained. The orange solid was mixed with activated carbon in methanol and stirred overnight, and then filtered to obtain a yellow solid; then, the yellow solid was transferred to a mixture of ethyl acetate and acetonitrile (the volume ratio of the two was 1:1) for recrystallization to obtain a white intermediate.
[0045] The white intermediate and lithium difluorooxalatoborate (LiDFOB) were mixed in deionized water at a molar ratio of 1:1.1, and then 3 volumes of dichloromethane were added to the mixture to separate the mixture into layers, and the dichloromethane phase containing the crude ionic liquid 1 was collected, and the aqueous phase was recovered by using the same amount of dichloromethane for two weeks (i.e., three times the volume of the aqueous phase) to maximize the yield; the dichloromethane phase containing the crude ionic liquid 1 was then washed with deionized water for three weeks, and the dichloromethane was removed by rotary evaporation to obtain the crude ionic liquid 1 (wherein, whether the crude ionic liquid 1 contained bromide ion impurities was determined by mixing the crude ionic liquid 1 with AgNO3 / HNO3 solution).
[0046] The crude ionic liquid 1 was diluted in dichloromethane and transferred to a chromatographic column filled with alumina for purification, and then the purified material was dried at 70°C for 12 h under vacuum conditions to obtain ionic liquid 1. The main reaction equation of ionic liquid 1 is as follows:
[0047]
[0048] The only difference between the preparation processes of ionic liquid 2 and ionic liquid 1 is that lithium difluorooxalatoborate (LiDFOB) is replaced by lithium tetrafluorooxalatophosphate (LiOTFP).
[0049] In a second aspect, an embodiment of the present application provides a solvent for a lithium-ion battery, comprising the ionic liquid and an organic solvent provided in the embodiment of the first aspect.
[0050] In the present application, the solvent for lithium-ion batteries contains, in addition to the organic solvent, the ionic liquid provided in the first embodiment. By taking advantage of the unique advantages of the ionic liquid, the solvent for lithium-ion batteries can stably exist under high voltage and high temperature conditions and have a high electrical conductivity, thereby enabling the corresponding battery to have excellent cycle performance when used under high voltage and high temperature conditions. At the same time, it can also effectively improve the problem of the corresponding battery being prone to flatulence when used under high voltage and high temperature conditions.
[0051] As an example, the mass percentage of the ionic liquid in the solvent is 30-50%, for example but not limited to any one of 30%, 35%, 40%, 45% and 50% or a range between any two of the mass percentages.
[0052] In this embodiment, the mass percentage of the ionic liquid in the solvent is limited to a specific range, so that the solvent contains a relatively suitable mass percentage of the ionic liquid, thereby making the corresponding battery have a better cycle performance when used under high voltage and high temperature conditions and can also more effectively improve the problem of the corresponding battery being prone to flatulence when used under high voltage and high temperature conditions; at the same time, it can also make the corresponding battery have a relatively excellent safety performance.
[0053] It should be noted that the type of organic solvent is not limited and can be selected according to routine practices in the art.
[0054] As an example, the organic solvent is at least one selected from fluoroethylene carbonate, bisfluoroethylene carbonate, trifluoroethyl methyl carbonate, bis(2,2,2-trifluoroethyl) carbonate, 3,3,3-trifluoropropylene carbonate and methyl hexafluoroisopropyl carbonate.
[0055] In this embodiment, the technical solution provided in the embodiment of the present application is applicable to a wide variety of organic solvents and can provide a wide variety of feasible implementation plans, thereby facilitating the promotion and application of the technical solution provided in the present application.
[0056] It should be noted that the components and their amounts not specifically described or limited in the solvent for lithium-ion batteries can be set according to conventional selection in the art.
[0057] In a third aspect, an embodiment of the present application provides a lithium-ion battery electrolyte, comprising a lithium-ion battery solvent, a lithium salt, and an additive as provided in the embodiment of the second aspect.
[0058] In the present application, the lithium-ion battery electrolyte includes a lithium-ion battery solvent as provided in the second embodiment. Since the solvent contains an ionic liquid with a specific structure, the corresponding battery can have relatively excellent cycle performance when used under high voltage and high temperature conditions. At the same time, it can also effectively improve the problem that the corresponding battery is prone to flatulence when used under high voltage and high temperature conditions.
[0059] It should be noted that the type of lithium salt is not limited and can be selected according to conventional methods in the art.
[0060] As an example, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorobis(oxalatophosphate), lithium tetrafluorooxalatophosphate, lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonyl)imide and lithium bis(oxalatoborate).
[0061] In this embodiment, the technical solution provided in the embodiment of the present application is applicable to a wide variety of lithium salts and can provide a wide variety of feasible implementation plans, thereby facilitating the promotion and application of the technical solution provided in the present application.
[0062] As an example, the mass percentage of lithium salt in the electrolyte is 10-18%, such as but not limited to any one of 10%, 12%, 14%, 16% and 18% or a range between any two of the mass percentages.
[0063] In this embodiment, the mass percentage of lithium salt in the electrolyte is limited to a specific range, so that the electrolyte has a lithium salt with a relatively suitable mass percentage, so that the electrolyte has relatively excellent electrical conductivity, and thus the corresponding battery has relatively excellent cycle performance when used under high voltage and high temperature conditions.
[0064] It should be noted that the types of additives are not limited and can be selected and set according to routine selection in the art.
[0065] As an example, the additive is selected from at least one of 1,3 propane sultone, 1,4 butane sultone, allyl 1,3 sultone, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluorooxalatephosphate, lithium difluorooxalatephosphate, tetravinylsilane, tripropylene phosphate, tetravinyltin, hexamethylene diisocyanate and difluoropyridine.
[0066] In this embodiment, the technical solution provided in the embodiment of the present application is applicable to a wide variety of additives and can provide a wide variety of feasible implementation plans, thereby facilitating the promotion and application of the technical solution provided in the present application.
[0067] As an example, the mass percentage of the additive in the electrolyte is 0.5-5%, for example but not limited to any one of 0.5%, 1%, 2%, 3%, 4% and 5% or a range between any two of them.
[0068] In this embodiment, the mass percentage of the additive in the electrolyte is limited to a specific range, so that the electrolyte has a relatively suitable mass percentage of the additive, so that the corresponding battery has relatively excellent cycle performance when used under high voltage and high temperature conditions.
[0069] It should be noted that the components and their amounts in the lithium-ion battery electrolyte that are not particularly described or limited can be set according to conventional selection in the art.
[0070] In a fourth aspect, an embodiment of the present application provides a lithium-ion battery, comprising a shell, an electrode assembly, and an electrolyte as provided in the embodiment of the third aspect, wherein the electrode assembly is contained in the shell; and the electrolyte is contained in the shell.
[0071] In the present application, the lithium-ion battery includes the electrolyte provided in the first aspect embodiment, and the unique advantages of the electrolyte are utilized to enable the lithium-ion battery to have relatively excellent cycle performance when used under high voltage and high temperature conditions.
[0072] As an example, in the battery positive electrode of the electrode assembly, the positive electrode active material is selected from at least one of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel manganese oxide and lithium cobalt oxide.
[0073] In this embodiment, the technical solution provided in the embodiment of the present application can be applied to the above-mentioned various positive electrode active material systems, providing more feasible implementation plans, thereby facilitating the promotion and application of the technical solution provided in the embodiment of the present application.
[0074] As an example, in the battery negative electrode of the electrode assembly, the negative electrode active material is selected from at least one of graphite, soft carbon, hard carbon, silicon, silicon oxides and silicon-carbon composites.
[0075] In this embodiment, the technical solution provided in the embodiment of the present application can be applied to the above-mentioned various negative electrode active material systems, providing more feasible implementation plans, thereby facilitating the promotion and application of the technical solution provided in the embodiment of the present application.
[0076] It should be noted that any functional device not specifically described or limited in the lithium-ion battery may be configured according to conventional selection in the art.
[0077] In a fifth aspect, an embodiment of the present application provides an electrical device, comprising a lithium-ion battery as provided in the embodiment of the fourth aspect.
[0078] It should be noted that there is no limitation on the types of electrical equipment, such as mobile phones, portable devices, laptops, electric vehicles, electric cars, ships, electric aircraft, spacecraft, electric toys, energy storage devices and electric tools.
[0079] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0080] Example
[0081] The preparation method of ionic liquid 1 comprises the following steps:
[0082] 0.1 mol of N-methylpiperidine and 0.1 mol of 1-bromomethane were added to 50 g of acetonitrile under a nitrogen atmosphere and then heated under reflux and stirred at 80°C for 24 hours. After the acetonitrile in the mixture was volatilized, an orange solid was obtained. The orange solid was mixed with activated carbon in methanol and stirred overnight, and then filtered to obtain a yellow solid; then, the yellow solid was transferred to a mixture of ethyl acetate and acetonitrile (the volume ratio of the two was 1:1) for recrystallization to obtain a white intermediate.
[0083] The white intermediate and lithium difluorooxalatoborate (LiDFOB) were mixed in deionized water at a molar ratio of 1:1.1, and then 3 volumes of dichloromethane were added to the mixture to separate the mixture into layers. The dichloromethane phase containing the crude ionic liquid 1 was collected, and the aqueous phase was recovered by using the same amount of dichloromethane for two weeks (i.e., three times the volume of the aqueous phase) to maximize the yield; the dichloromethane phase containing the crude ionic liquid 1 was then washed with deionized water for three weeks, and the dichloromethane was removed by rotary evaporation to obtain the crude ionic liquid 1.
[0084] The crude ionic liquid 1 was diluted in dichloromethane and transferred to a chromatographic column filled with alumina for purification. The purified material was then dried under vacuum at 70° C. for 12 h to obtain ionic liquid 1.
[0085] The preparation method of ionic liquid 2 comprises the following steps:
[0086] 0.1 mol of N-methylpiperidine and 0.1 mol of 1-bromomethane were added to 50 g of acetonitrile under a nitrogen atmosphere and then heated under reflux and stirred at 80°C for 24 hours. After the acetonitrile in the mixture was volatilized, an orange solid was obtained. The orange solid was mixed with activated carbon in methanol and stirred overnight, and then filtered to obtain a yellow solid; then, the yellow solid was transferred to a mixture of ethyl acetate and acetonitrile (the volume ratio of the two was 1:1) for recrystallization to obtain a white intermediate.
[0087] The white intermediate and lithium tetrafluorooxalate phosphate were mixed in deionized water at a molar ratio of 1:1.1, and then 3 volumes of dichloromethane were added to the mixture to stratify the mixture, and the dichloromethane phase containing the crude ionic liquid 2 was collected, and the aqueous phase was recovered by using the same amount of dichloromethane for two weeks (i.e., three times the volume of the aqueous phase) to maximize the yield; the dichloromethane phase containing the crude ionic liquid 2 was then washed with deionized water for three weeks, and the dichloromethane was removed by rotary evaporation to obtain the crude ionic liquid 2.
[0088] The crude ionic liquid 2 was diluted in dichloromethane and transferred to a chromatographic column filled with alumina for purification. The purified material was then dried under vacuum at 70° C. for 12 h to obtain ionic liquid 2.
[0089] The prepared ionic liquid 1 or ionic liquid 2, trifluoroethyl methyl carbonate (FEMC) and fluoroethylene carbonate (FEC) are mixed in a mass ratio of 2:70:28 to obtain a solvent for a lithium ion battery; then additives (tetravinylsilane, propenyl 1,3-sultone and lithium difluorooxalatoborate) and a lithium salt (lithium hexafluoroborate) are added to the solvent and mixed to obtain an electrolyte; in the electrolyte, the mass percentages of the solvent, tetravinylsilane, propenyl 1,3-sultone, lithium difluorooxalatoborate and the lithium salt are 85.7:0.5:0.3:0.5:13, that is, in the electrolyte, the mass percentages of the solvent: the additive: the lithium salt are 85.7:1.3:13.
[0090] The composition and amount of the lithium salt and additives in the subsequent examples and comparative examples are the same, the only difference is the composition of the solvent, which can be seen in Table 1.
[0091] Table 1
[0092] sample Ionic liquid 1(%) Ionic liquid 2 (%) FEMC(%) FEC(%) Example 1 5 — 70 25 Example 2 10 — 70 20 Example 3 20 — 70 10 Example 4 30 — 70 0 Example 5 50 — 50 0 Example 6 80 — 20 0 Example 7 — 20 70 10 Example 8 — 30 70 0 Example 9 — 50 50 0 Comparative Example 1 — — 50 50 Comparative Example 2 — — 70 30
[0093] It should be noted that “—” means no addition.
[0094] Test Example 1
[0095] Structure determination of ionic liquids
[0096] Test method:
[0097] The structures of the ionic liquids prepared in Example 1 and Example 7 were tested using a nuclear magnetic resonance instrument (model: Bruker 400 MHz), and the specific parameters were as follows: deuterated acetonitrile was used as the solvent, tetramethylsilane was used as the internal standard (δ=0 ppm), and the compound structure was confirmed by hydrogen nuclear magnetic resonance (1HNMR).
[0098] The structure of ionic liquid 1 was determined by using a nuclear magnetic resonance spectrometer (model: Bruker 400 MHz) to test the structure of the ionic liquid prepared in Example 1. The test results are shown in Figure 1 ,Depend on Figure 1 It can be seen that at the position of δ=3.27 (s, 3H), there is a single peak with 3 H atoms, representing the CH3 group N-CH3 connected to N; at the position of δ=3.24 (t, 2H), there are 2 H atoms, split into triplet peaks, representing 3 CH2 groups connected to N; N-(CH2)3; at the position of δ=2.98 (s, 2H), there is a single peak with 2 H, representing CH2; near δ=1.78 (t, 4H), there are 4 H atoms, split into triplet peaks, representing N-(CH2CH2)3; at the position of δ=1.73~1.61 (m, 2H), there are 2 hydrogens, split into multiple peaks, representing multiple symmetrical structure CH2 groups; at the position of δ=0.91 (t, 3H)], there are 3 hydrogens, split into triplet peaks, representing CH3 groups; it is proved that the structural formula of the prepared ionic liquid 1 is formula I.
[0099] The structure of ionic liquid 2 was determined by using a nuclear magnetic resonance spectrometer (model: Bruker 400 MHz) to test the structure of the ionic liquid prepared in Example 7. The test results are shown in Figure 2 ,Depend on Figure 2 It can be seen that at the position of δ=3.30 (s, 3H), there is a single peak with 3 H atoms, representing the N-connected CH3 group N-CH3; at the position of δ=3.22 (t, 2H), there are 2 H atoms, split into triplet peaks, representing 3 N-connected CH2 groups; N-(CH2)3; at the position of δ=1.8~1.70 (m, 2H), there are 2 hydrogens, split into multiple peaks, representing multiple symmetrical structure CH2 groups; at the position of δ=1.60 (d, 2H), there are 2 hydrogens, a doublet peak, representing multiple symmetrical structure CH2 groups, and at the position of δ=0.95 (t, 3H)] there are 3 hydrogens, split into triplet peaks, representing CH3 groups; it is proved that the structural formula of the prepared ionic liquid 2 is formula II.
[0100] Test Example 2
[0101] Oxidation potential test of electrolyte
[0102] Test method: The platinum sheet is used as the working electrode and the lithium sheet is used as the counter electrode. The platinum electrode electrolytic cell is assembled, and the electrolytes of Example 5 and Comparative Example 1 are added respectively. The LSV test is performed using an electrochemical workstation with a scanning voltage of 3.0 to 7.0 V.
[0103] The test results can be found in Figure 3 ,Depend on Figure 3It can be seen that the oxidation potential in Example 5 is significantly higher than that in Comparative Example 1, indicating that the oxidation potential of the solvent can be increased by replacing part of the conventional organic solvent in the solvent with the ionic liquid of the specific structure provided in the embodiment of the present application, thereby being more conducive to application under high voltage.
[0104] Test Example 3
[0105] Electrical performance test
[0106] Test method:
[0107] First, the lithium-ion battery electrolytes prepared in Examples 1 to 9 and Comparative Examples 1 to 2 were numbered, and then the conductivity of each electrolyte was tested; then, each electrolyte was assembled into a battery, and the capacity retention rate of each battery sample after 500 cycles at 25°C, the capacity retention rate after 500 cycles at 60°C, the expansion rate after 7 days of storage at 60°C, and the safety performance were tested and statistically reported in Table 2.
[0108] The battery is assembled as follows:
[0109] S1 is mixed with LiNi in a mass ratio of 96.8:2:1.2 0.5 Mn 1.5 O4 (positive electrode active material), conductive carbon black (conductive agent) and polyvinylidene fluoride (binder) are dispersed in N-methyl-2-pyrrolidone to obtain positive electrode slurry; then, the positive electrode slurry is evenly coated on both sides of the aluminum foil; then, after drying, calendering and vacuum drying, an aluminum lead wire is welded with an ultrasonic welder to obtain a positive electrode sheet with a thickness of 125μm.
[0110] S2 is prepared by mixing graphite (negative electrode active material), conductive carbon black (conductive agent), styrene-butadiene rubber and carboxymethyl cellulose (binder) in a mass ratio of 95:1.5:1.5:2 and dispersing the mixture in deionized water to obtain a negative electrode slurry. The negative electrode slurry is then coated on both sides of a copper foil. The mixture is then dried, rolled and vacuum dried in sequence, and a nickel lead wire is welded on the mixture with an ultrasonic welder to obtain a negative electrode sheet having a thickness of 125 μm.
[0111] S3 prepares a bare battery cell by winding the prepared positive electrode sheet, negative electrode sheet and PE ceramic diaphragm, and then injects the bare battery cell and shell as well as the electrolyte group prepared in Examples 1 to 9 and Comparative Examples 1 to 2 into the dried battery, and completes the battery assembly through packaging, standing, formation, shaping and capacity testing.
[0112] The test steps for relevant electrical properties are as follows:
[0113] (1) Conductivity test:
[0114] Take 50g of electrolyte and put it into a beaker. Then transfer the beaker containing the electrolyte into a 25℃ constant temperature water bath, keep the temperature at 25℃, and measure the conductivity using a conductivity tester.
[0115] (2) Battery capacity retention test after 500 cycles at 25°C:
[0116] The battery was placed at 25°C, and the battery was charged and discharged in a voltage range of 3.5 to 4.9V using a current of 0.5C, and the discharge capacity of the 500th cycle was recorded.
[0117] (3) Battery capacity retention test after 100 cycles at 60°C:
[0118] The battery was placed at 60°C, and the battery was charged and discharged in a voltage range of 3.5 to 4.9V using a current of 0.5C, and the discharge capacity of the 500th cycle was recorded.
[0119] (4) Expansion test of batteries stored at 60°C for 7 days:
[0120] Charge at 25℃ with a constant current of 0.5C to 4.9V, and charge at a constant voltage of 4.9V to a cut-off current of 0.05C. Remove the battery and use a thickness tester to test its initial thickness, which is T1. Then transfer the battery to 60℃ and let it stand for 7 days. Use a thickness tester to test its thickness after 7 days, which is T2.
[0121] The calculation formula is as follows:
[0122] 500-cycle capacity retention rate (%) = (500th cycle discharge capacity / 1st cycle discharge capacity) × 100%.
[0123] Storage at 60°C for 7 days: Expansion ratio (%) = (T2-T1) / T1×100%.
[0124] (5) Battery safety performance needle penetration test:
[0125] Charge at 0.5C constant current to 4.9V at 25℃, and charge at 4.9V constant voltage to a cut-off current of 0.05C. Remove the battery and fix it on a special acupuncture device. Use a 5mm diameter high-temperature resistant steel needle (the cone angle of the needle tip is 45°~50°, and the surface of the needle is smooth, free of rust, oxide layer and oil stains) to penetrate the battery plate at right angles to the direction of the battery plate at a speed of 25mm / s. The penetration position is close to the geometric center of the punctured surface. The steel needle stays in the battery and is observed for 1 hour.
[0126] Table 2
[0127]
[0128]
[0129] Referring to Table 2, it can be seen from the test results of Examples 1 to 9 and Comparative Examples 1 to 2 that replacing part of the conventional organic solvent in the solvent with the ionic liquid 1 or ionic liquid 2 with a specific structure provided in the embodiments of the present application is helpful to improve the conductivity of the corresponding solvent. At the same time, it can also enable the corresponding battery to have a relatively excellent cycle performance when used under high voltage and high temperature conditions, and can also effectively improve the problem of easy flatulence of the corresponding battery when used under high voltage and high temperature conditions.
[0130] It can be seen from the test results of Examples 1 to 6 that limiting the amount of ionic liquid in the solvent to a specific range of 30 to 50% helps to better improve the conductivity of the corresponding solvent. At the same time, it can also enable the corresponding battery to have better cycle performance when used under high voltage and high temperature conditions, and can also more effectively improve the problem of easy flatulence of the corresponding battery when used under high voltage and high temperature conditions.
[0131] It can be seen from the test results of Examples 1 to 9 that when the mass proportion of ionic liquid 1 or ionic liquid 2 in the solvent exceeds 30%, the safety performance of the corresponding battery when used under high voltage and high temperature conditions can be effectively improved.
[0132] From the test results of Examples 3 to 5 and Examples 7 to 9, it can be seen that the effects of ionic liquid 1 and ionic liquid 2 are substantially equivalent, and it can be selected to add only one of them or both of them to the solvent.
[0133] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
Claims
1. An ionic liquid, characterized in that It includes ionic liquid 1 and / or ionic liquid 2, wherein the structural formula of the ionic liquid 1 is as shown in Formula I, and the structural formula of the ionic liquid 2 is as shown in Formula II:
2. A solvent for lithium ion batteries, characterized in that: The invention comprises the ionic liquid as claimed in claim 1 and an organic solvent.
3. The solvent for lithium ion batteries according to claim 2, characterized in that The mass percentage of the ionic liquid in the solvent is 30-50%.
4. The solvent for lithium ion batteries according to claim 2, characterized in that The organic solvent is at least one selected from fluoroethylene carbonate, bisfluoroethylene carbonate, trifluoroethyl methyl carbonate, bis(2,2,2-trifluoroethyl) carbonate, 3,3,3-trifluoropropylene carbonate and methyl hexafluoroisopropyl carbonate.
5. A lithium ion battery electrolyte, characterized in that: The invention comprises the solvent for lithium ion battery according to any one of claims 2 to 4, a lithium salt and an additive.
6. The lithium ion battery electrolyte according to claim 5, characterized in that: The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorobis(oxalatophosphate), lithium tetrafluorooxalatophosphate, lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonyl)imide and lithium bis(oxalatoborate).
7. The lithium ion battery electrolyte according to claim 6, characterized in that: The mass percentage of the lithium salt in the electrolyte is 10-18%.
8. The lithium ion battery electrolyte according to claim 5, characterized in that: The additive is selected from at least one of 1,3 propane sultone, 1,4 butane sultone, 1,3 propenyl sultone, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluorooxalatephosphate, lithium difluorooxalatephosphate, tetravinylsilane, tripropylene phosphate, tetravinyltin, hexamethylene diisocyanate and difluoropyridine.
9. The lithium-ion battery electrolyte according to claim 8, characterized in that: The mass percentage of the additive in the electrolyte is 0.5-5%.
10. A lithium ion battery, characterized in that: include: case; an electrode assembly, the electrode assembly being accommodated in the housing; as well as The electrolyte according to any one of claims 5 to 9, wherein the electrolyte is contained in the housing.
11. The lithium ion battery according to claim 10, characterized in that: In the battery positive electrode of the electrode assembly, the positive electrode active material is selected from at least one of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel manganese oxide and lithium cobalt oxide.
12. The lithium ion battery according to claim 10, characterized in that: In the battery negative electrode of the electrode assembly, the negative electrode active material is selected from at least one of graphite, soft carbon, hard carbon, silicon, silicon oxides and silicon-carbon composites.
13. An electrical equipment, characterized in that: The invention comprises a lithium ion battery as claimed in any one of claims 10 to 12.
Citation Information
Patent Citations
Ionic liquid mixed electrolyte for lithium ion battery
CN103094610A
High voltage electrolyte for lithium ion battery
CN105591155A
Electronic pen in a system that analyzes the user's learning characteristics using log data of the electronic pen
KR102807750B1
Chemically inert additives for electrochemical cells
US20240120543A1
Cited By
High-energy-density solid-state lithium ion battery and preparation method thereof
CN120221757A
High energy density solid-state lithium-ion batteries and their preparation methods
CN120221757B